(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate changes in sperm DNA fragmentation rate and conventional semen parameters in male patients with varicocele before and after surgical treatment. Subjects and methods: A systematic review of published systematic reviews and meta-analyses (overview of systematic reviews) together with primary studies on male patients with clinical varicocele who underwent surgical treatment (microsurgical or non-microsurgical varicocelectomy), with assessment of semen parameters and sperm DNA fragmentation rate before and at least 3 months after surgery. Results: All included studies reported a statistically significant decrease in sperm DNA fragmentation rate after varicocelectomy, with a reduction ranging from 3% to 11% depending on the follow‑up time point. Semen parameters (sperm concentration, progressive motility, and morphology) also significantly improved after surgery, especially in the microsurgical varicocelectomy group. Conclusion: Current evidence suggests a trend toward improvement in both sperm DNA fragmentation rate and conventional semen parameters after varicocelectomy in infertile men with clinical varicocele, particularly with the microsurgical technique. However, well‑standardized systematic reviews are needed to confirm these findings.